2008
DOI: 10.2165/00023210-200822110-00004
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances in Patients with Schizophrenia

Abstract: Difficulties initiating or maintaining sleep are frequently encountered in patients with schizophrenia. Disturbed sleep can be found in 30-80% of schizophrenic patients, depending on the degree of psychotic symptomatology. Measured by polysomnography, reduced sleep efficiency and total sleep time, as well as increased sleep latency, are found in most patients with schizophrenia and appear to be an important part of the pathophysiology of this disorder. Some studies also reported alterations of stage 2 sleep, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
271
1
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(303 citation statements)
references
References 123 publications
11
271
1
10
Order By: Relevance
“…In addition to potential anti-tumor activity, studies and clinical trials of olanzapine have demonstrated its efficacy in the prevention of chemotherapy-induced nausea and emesis (Navari, 2014). Some subjects without psychiatric disorders also experience sleep continuity and efficiency as well as increased stage III/IV sleep in the olanzapine treated groups (Cohrs, 2008). All these attributes would be beneficial to glioblastoma patients as well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to potential anti-tumor activity, studies and clinical trials of olanzapine have demonstrated its efficacy in the prevention of chemotherapy-induced nausea and emesis (Navari, 2014). Some subjects without psychiatric disorders also experience sleep continuity and efficiency as well as increased stage III/IV sleep in the olanzapine treated groups (Cohrs, 2008). All these attributes would be beneficial to glioblastoma patients as well.…”
Section: Discussionmentioning
confidence: 99%
“…As well as subjectively reported poor sleep quality, individuals with schizophrenia show abnormal architectural properties of sleep, including increased sleep latency, reduced REM latency, REM density, sleep efficiency, total sleep time and duration of SWS (Cohrs 2008). Additionally, individuals with schizophrenia often exhibit severe circadian disruption, including phase delays and advances, free--running rhythms, and irregular sleep--wake scheduling (Wulff et al 2010).…”
Section: Sleep and Schizophrenia: While Childhood Onset Schizophreniamentioning
confidence: 99%
“…Furthermore, there was great variability of sleep duration and increased nocturnal time awakening in remitted BPD outpatients (21). Some studies conducted on drug free patients, found that decreased sleep efficiency, reduced total sleep time, and elevated sleep latency in schizophrenia (22).…”
Section: Biological Rhythms and Psychiatrymentioning
confidence: 99%